Challenges and Opportunities for news media and journalism in an increasingly digital, mobile, and social media environment - Nielsen, R; Cornia, A; Kalogeropoulos, A (Reuters Institute for the Study of Journalism, 2016)
Commissioned by the Council of Europe, this report reviews challenges and opportunities for news media and journalism in today’s changing media environment. As more people get news via mobile devices and rely on social media and other intermediaries for accessing and finding news, legacy media are becoming relatively less important distributors of news and are under growing pressure as existing sources of revenue decline or stagnate. Instead, a limited number of large technology companies play an increasingly important role both in the distribution of news and in digital advertising. Domination by these new players together with consolidation and cost-cutting elsewhere in the media landscape can reduce media pluralism by undermining the diversity of news production. The move to an increasingly digital, mobile, and social media environment also means that forms of policy intervention designed for twentieth century media environments will need reform to be effective and efficient in this century.